Absolute pitch and serial digit recall under irrelevant speech conditions: investigating automatic pitch class labelling through cognitive psychology - Steingaszner, Severian Geza (Stellenbosch : Stellenbosch University, 2024)
Thesis (MMus)--Stellenbosch University, 2024.